Resistance to molecular therapies for hepatocellular carcinoma - Villanueva, Augusto (Springer, 2017)
And Future Challenges for Cancer Stem Cell Research in HCCReferences; Clinical and Preclinical Perspectives on Mechanisms of Sorafenib Resistance in Hepatocellular Carcinoma; Introduction; Lessons from Second-Line Clinical Trials in HCC; Preclinical and Translational Data on Mechanisms of Sorafenib Resistance; Future Perspectives; References; Radiological Assessment of Response to Palliative Treatments in Hepatocellular Carcinoma; Introduction; mRECIST Assessment at Baseline; mRECIST Evaluation of Tumor Response; Assessment of Response to Loco-Regional Therapies.
Includes index.
Keywords: Liver -- Cancer -- Chemotherapy.; Drug resistance in cancer cells.; elektronické knihy; electronic books